Differences in Meibum and Tear Lipid Composition and Conformation. Issue 1 (January 2020) - Borchman, Douglas; Ramakrishnan, Varun; Henry, Collin; Ramasubramanian, Aparna
Abstract : Purpose: The compositional, structural, and functional relationships of meibum may provide insights into the loss of tear film stability. Although the conformation of meibum lipids has been studied rigorously, that of tear lipids has not. Methods: Tear lipids (TLHSCT ) and meibum (MHSCT ) from patients who had hematopoietic stem cell transplantation were pooled prospectively. The infrared spectra of meibum from donors with (MMGD ) and without (Mn ) meibomian gland dysfunction were retrospectively analyzed to measure the lipid composition and structure. The infrared CH stretching region was used to measure the relative content of CH3 and CH2 moieties in the meibum. Results: The 3 major findings of the current study are as follows: 1) compared with Mn, MHSCT and MMGD had 18% fewer CH3 moieties; 2) compared with MHSCT, the phase transition temperature, cooperativity, and order were approximately 20% greater for TLHSCT ; and 3) compared with Mn and MMGD, MHSCT and TLHSCT contained fewer double bonds. Conclusions: Tear lipids are more ordered than meibum lipids, which could have functional consequences. The human meibum peak height ratio of the CH3 /CH2 bands is not a factor related to tear film stability with age or sex. The amount of CH3 moieties relative to CH2 moieties and saturation could contribute to a higher meibum lipid order associated with a younger age, meibomian gland dysfunction, and dry eye from hematopoietic stem cell transplantation. Therefore, the hydrocarbon order may be a marker of or contribute to an unstable tear film layer.